2003
DOI: 10.1109/tsp.2003.816754
|View full text |Cite
|
Sign up to set email alerts
|

Gaussian sum particle filtering

Abstract: Abstract-In this paper, we use the Gaussian particle filter introduced in a companion paper to build several types of Gaussian sum particle filters. These filters approximate the filtering and predictive distributions by weighted Gaussian mixtures and are basically banks of Gaussian particle filters. Then, we extend the use of Gaussian particle filters and Gaussian sum particle filters to dynamic state space (DSS) models with non-Gaussian noise. With non-Gaussian noise approximated by Gaussian mixtures, the no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
227
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(227 citation statements)
references
References 24 publications
0
227
0
Order By: Relevance
“…However, a major disadvantage of SISR is the computational complexity, a large part of which comes from a procedure called resampling [85]. The Gaussian sum particle filter (GSPF) [85] implements the PF assuming Gaussian mixture distributions for the system and measurement noises. The GPF [85] is quite similar to the SISR filter by the fact that importance sampling is used to obtain particles.…”
Section: ) Particle Filteringmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a major disadvantage of SISR is the computational complexity, a large part of which comes from a procedure called resampling [85]. The Gaussian sum particle filter (GSPF) [85] implements the PF assuming Gaussian mixture distributions for the system and measurement noises. The GPF [85] is quite similar to the SISR filter by the fact that importance sampling is used to obtain particles.…”
Section: ) Particle Filteringmentioning
confidence: 99%
“…The Gaussian sum particle filter (GSPF) [85] implements the PF assuming Gaussian mixture distributions for the system and measurement noises. The GPF [85] is quite similar to the SISR filter by the fact that importance sampling is used to obtain particles. However, unlike the SISR filters, resampling is not required in the GPF.…”
Section: ) Particle Filteringmentioning
confidence: 99%
“…In [45], Stordal et al identify a connection between the EnKF and the Gaussian mixture filter [46,47]. The EnKF is viewed as a special case of Gaussian mixture filter with the added constraint that all the weights are uniform.…”
Section: Enkf With Gaussian Mixture Modelsmentioning
confidence: 99%
“…The next three subsections are based on methods for calculating the predicted mean and covariance, in equations (7) and (8), and then computing (14)(15)(16)(17)(18) in order to compute the mean and covariance update, in equations (12) and (13). The technique presented in the final subsection takes a different approach in that it attempts to approximate the Gaussian Bayes recursion, in equations (5) and (6), directly through Monte Carlo integration and importance sampling.…”
Section: Gaussian Filteringmentioning
confidence: 99%
“…This approach has been extended for more general probability distributions [17] within a Gaussian sum framework, and we have shown that this approach can be extended to intensity functions [18]. Suppose that the Gaussian posterior density, N (ξ; m k−1 , P k−1 ), is projected through nonlinear state function ϕ k−1 (·) with process noise Q k−1 .…”
Section: Gaussian Particle Filteringmentioning
confidence: 99%